Study of regional inequalities: case of Bulgaria - Ivanov, Ivaylo (Business, Management and Economics Engineering, 2018)
The sustainable development of a country depends on many factors. One of them is the balanced development of regions. The aim of this research is to study the inequalities between regions (NUTS 3 level) in Bulgaria by application of the Regional Competitiveness Index (RCI), a tool, which is based on 10 important for regional development indicators. The paper presents the last RCI ranking list (for the 2016 year) and analyses and compares it with the ranking lists for previous years. The results show significant inequalities between the capital region and other regions for the whole period and relative small imbalances between other regions. The RCI ascertained relatively stable groups of most competitive and most non-competitive regions.